Composite particles, binder composition for non-aqueous secondary batteries, and non-aqueous secondary battery electrode
By using composite particles composed of copolymers copolymerized by monomers (a1) and monomers (a2) and tackifiers as binders, the problem of insufficient circulation characteristics of the non-aqueous secondary battery electrodes in the prior art is solved, and better battery performance is achieved.
Patent Information
- Application Number
- CN202380066958.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-22
- Filing Date
- 2023-09-08
- Publication Date
- 2025-04-25
AI Technical Summary
The adhesives of existing non-aqueous secondary batteries are difficult to improve the circulation characteristics of the electrodes, resulting in insufficient battery performance.
Compound particles composed of copolymers copolymerized by monomers (a1) and monomers (a2) and tackifier are used as the binder, and the adhesion of the electrode active substance is improved through the synergistic effect of the copolymer and tackifier.
It significantly improves the circulation characteristics of non-aqueous secondary batteries, extends the service life of the battery, and improves the overall performance of the battery.
Smart Images

Figure BDA0005316838700000071 
Figure BDA0005316838700000072 
Figure BDA0005316838700000073
Abstract
Description
Technical Field
[0001] The present invention relates to composite particles, a binder composition for non-aqueous secondary batteries, a slurry for non-aqueous secondary battery electrodes, a non-aqueous secondary battery electrode, a non-aqueous secondary battery, and a method for producing composite particles.
[0002] This application claims priority based on Japanese Patent Application No. 2022-151135 filed in Japan on September 22, 2022, the contents of which are incorporated herein by reference. Background Art
[0003] Non-aqueous secondary batteries are widely used as power sources for notebook computers, mobile phones, power tools, electronic / communication equipment, etc., because they can be miniaturized and lightweight. In recent years, non-aqueous secondary batteries are also used as power sources for electric vehicles and hybrid vehicles, etc. As a representative example of non-aqueous secondary batteries, lithium-ion secondary batteries can be cited.
[0004] A non-aqueous secondary battery comprises a positive electrode with a metal oxide or the like as an active material, a negative electrode with a carbon material such as graphite as an active material, and an electrolyte. The positive electrode and the negative electrode have a current collector and an electrode active material layer formed on the current collector. The electrode active material layer generally comprises a binder that binds the active materials to each other and to the current collector, and fixes the electrode active material layer to the current collector.
[0005] Conventionally, as binders that can be used in non-aqueous secondary batteries, those described in Patent Documents 1 and 2 are known.
[0006] Patent Document 1 describes a binder composition for secondary battery electrodes containing 100 parts by mass of at least one polymer aqueous dispersion selected from styrene-butadiene copolymer latex and acrylic emulsion, and 1 to 20 parts by mass of a nonionic surfactant.
[0007] Patent Document 2 describes a binder for lithium ion secondary battery electrodes having a glass transition temperature of 30° C. or less, obtained by emulsion polymerization of ethylenically unsaturated monomers containing 15 to 70% by mass of styrene, ethylenically unsaturated carboxylic acid esters and ethylenically unsaturated carboxylic acids and an internal crosslinking agent as essential components in the presence of a surfactant.
[0008] Patent Document 3 describes a tire puncture sealant containing an acrylic emulsion, an antifreeze agent, and a tackifier.
[0009] Patent Document 4 describes a water-dispersible acrylic adhesive tape or sheet for transporting electronic components, which has an adhesive layer formed of an acrylic adhesive containing an acrylic emulsion polymer as a main component. Patent Document 4 also describes an acrylic emulsion polymer obtained by emulsion polymerization of an acrylic monomer mixture containing a carboxyl group-containing monomer. Patent Document 4 also discloses that the acrylic adhesive contains a rosin-based or terpene-based tackifier having a softening point of 100° C. or higher.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2014-239070
[0013] Patent Document 2: Japanese Patent Application Publication No. 2011-243464
[0014] Patent Document 3: Japanese Patent Application Publication No. 2007-224248
[0015] Patent Document 4: Japanese Patent Application Publication No. 2008-285221 Summary of the invention
[0016] Problems to be solved by the invention
[0017] In recent years, nonaqueous secondary batteries have been strongly required to have higher output, higher capacity, longer life, etc. Binders that can be used in nonaqueous secondary batteries are required to be able to improve the cycle characteristics of nonaqueous secondary batteries having electrodes using the binders.
[0018] The present invention has been made in view of the above circumstances, and an object thereof is to provide composite particles that can be used as a material for a binder capable of forming an electrode for a non-aqueous secondary battery having excellent cycle characteristics, and a method for producing the composite particles.
[0019] In addition, the object of the present invention is to provide a non-aqueous secondary battery adhesive composition comprising the composite particles of the present invention, which can form an electrode of a non-aqueous secondary battery that can obtain excellent cycle characteristics, a slurry for a non-aqueous secondary battery electrode, a non-aqueous secondary battery electrode that can obtain a non-aqueous secondary battery with excellent cycle characteristics, and a non-aqueous secondary battery having the electrode.
[0020] Means for solving problems
[0021] The present invention includes the following aspects.
[0022] A first aspect of the present invention provides the following composite particles.
[0023] [1] A composite particle comprising a copolymer and a thickener,
[0024] The copolymer has a first structural unit derived from a monomer (a1) and a second structural unit derived from a monomer (a2),
[0025] The monomer (a1) is a nonionic compound having only one ethylenically unsaturated bond.
[0026] The monomer (a2) is a compound having a carboxyl group and having only one ethylenically unsaturated bond.
[0027] The composite particles according to the first aspect of the present invention preferably have the features described in the following [2] to
[10] . It is also preferred that two or more of the features described in the following [2] to
[10] are arbitrarily combined.
[0028] [2] The composite particles according to [1], wherein at least a portion of the thickener is present in a particle structure composed of chain molecules of the copolymer.
[0029] [3] The composite particles according to [1] or [2], wherein the thickener is at least one selected from hydrogenated petroleum resins and terpene resins.
[0030] [4] The composite particles according to [3], wherein the thickener comprises a hydrogenated petroleum resin.
[0031] [5] The composite particles according to [4], wherein the softening point of the hydrogenated petroleum resin is 70°C to 140°C.
[0032] [6] The composite particles according to any one of [1] to [5], wherein the content of the thickener is 0.50 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the monomer components used in the production of the copolymer.
[0033] [7] The composite particles according to any one of [1] to [6], wherein the content of the second structural unit in all structural units of the copolymer is 0.10% by mass or more and 20% by mass or less.
[0034] [8] The composite particles according to any one of [1] to [7], wherein the copolymer has a third structural unit derived from the monomer (a3),
[0035] The monomer (a3) is a compound having a plurality of independent ethylenically unsaturated bonds.
[0036] [9] The composite particles according to [8], wherein the content of the third structural unit in all structural units of the copolymer is 0.010 mass % or more and 10 mass % or less.
[0037]
[10] The composite particle according to any one of [1] to [9], which is used for a binder for a non-aqueous secondary battery.
[0038] A second aspect of the present invention provides the following binder composition for a non-aqueous secondary battery.
[0039]
[11] A binder composition for a non-aqueous secondary battery, comprising the composite particles according to any one of [1] to [9] and an aqueous medium.
[0040] A third aspect of the present invention provides the following slurry for nonaqueous secondary battery electrodes.
[0041]
[12] A slurry for non-aqueous secondary battery electrodes, comprising the composite particles described in any one of [1] to [9], an electrode active material, and an aqueous medium,
[0042] The aqueous medium is one selected from water, a hydrophilic solvent, and a mixture containing water and a hydrophilic solvent.
[0043] A fourth aspect of the present invention provides the following nonaqueous secondary battery electrode.
[0044]
[13] A non-aqueous secondary battery electrode comprising the composite particles according to any one of [1] to [9].
[0045] A fifth aspect of the present invention provides the following nonaqueous secondary battery.
[0046]
[14] A non-aqueous secondary battery comprising the non-aqueous secondary battery electrode described in
[13] .
[0047] A sixth aspect of the present invention provides the following method for producing composite particles.
[0048]
[15] A method for producing composite particles, comprising a polymerization step of copolymerizing a raw material monomer (a) comprising a monomer (a1) and a monomer (a2) in the presence of a thickener,
[0049] The monomer (a1) is a nonionic compound having only one ethylenically unsaturated bond.
[0050] The monomer (a2) is a compound having a carboxyl group and having only one ethylenically unsaturated bond.
[0051] Effects of the Invention
[0052] According to the present invention, composite particles that can be used as a material for a binder capable of forming an electrode that can provide a non-aqueous secondary battery with excellent cycle characteristics and a method for producing the same can be provided.
[0053] Furthermore, according to the present invention, a binder composition for a non-aqueous secondary battery capable of forming an electrode for a non-aqueous secondary battery having excellent cycle characteristics and a slurry for a non-aqueous secondary battery electrode can be provided.
[0054] Furthermore, according to the present invention, it is possible to provide a nonaqueous secondary battery electrode capable of obtaining a nonaqueous secondary battery having excellent cycle characteristics, and a nonaqueous secondary battery having excellent cycle characteristics including the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 This is a schematic diagram for explaining the state of a composition including composite particles containing a thickener obtained by the production method of the present embodiment and an aqueous medium.
[0056] Figure 2 This is a schematic diagram for explaining the state of a composition including other composite particles containing a thickener and an aqueous medium obtained by the production method of this embodiment.
[0057] Figure 3 It is a comparative schematic diagram for explaining the state of a composition including copolymer particles, a thickener arranged separately from the copolymer particles, and an aqueous medium. DETAILED DESCRIPTION
[0058] In order to solve the above-mentioned problems and realize a binder that can form a non-aqueous secondary battery electrode that can obtain a non-aqueous secondary battery with excellent cycle characteristics, the inventors focused on copolymers formed by copolymerizing a monomer (a1) composed of a non-ionic compound having only one ethylenically unsaturated bond and a monomer (a2) composed of a compound having an anionic functional group and only one ethylenically unsaturated bond, as well as a thickener, and conducted in-depth research on binder materials containing them.
[0059] As a result, it is found that as long as the composite particles containing the copolymer formed by copolymerizing the monomer containing monomer (a1) and monomer (a2) and the thickener are used as the binder for non-aqueous secondary batteries. In the case of forming an electrode using such a binder for non-aqueous secondary batteries, the composite particles present between the electrode active material and between the electrode active material and the collector include copolymers and thickeners. Therefore, the synergistic effect brought by the copolymer and the thickener is fully utilized to become an electrode with good adhesion between the electrode active material and between the electrode active material and the collector. As a result, it is presumed that a non-aqueous secondary battery with excellent cycle characteristics and a non-aqueous secondary battery electrode can be obtained.
[0060] Furthermore, the present inventors produced an electrode using the composite particles as a binder for a non-aqueous secondary battery, confirmed that the non-aqueous secondary battery having the electrode had excellent cycle characteristics, and thus conceived the present invention.
[0061] Hereinafter, the composite particles of the present invention, the binder composition for non-aqueous secondary batteries, the slurry for non-aqueous secondary battery electrodes, the non-aqueous secondary battery electrodes, the non-aqueous secondary batteries, and the manufacturing method of the composite particles are described in detail. It should be noted that the present invention is not limited to the embodiments shown below. For example, the present invention can add, omit, replace, and change the number, amount, position, ratio, material, composition, type, sequence, etc. within the scope of the purpose of the present invention.
[0062] Here, the following terms used in this specification are explained.
[0063] The term "(meth)acrylic acid" is a general term for acrylic acid and methacrylic acid. The term "(meth)acrylate" is a general term for acrylate and methacrylate.
[0064] The "ethylenically unsaturated bond" refers to an ethylenically unsaturated bond having radical polymerizability unless otherwise specified.
[0065] In a polymer using a compound having an ethylenically unsaturated bond, the structural unit derived from the compound having an ethylenically unsaturated bond refers to a structural unit in which the chemical structure of the portion other than the ethylenically unsaturated bond in the compound having an ethylenically unsaturated bond is the same as the chemical structure of the portion of the structural unit in the polymer other than the portion corresponding to the ethylenically unsaturated bond. The ethylenically unsaturated bond of the compound changes to a single bond when forming a polymer. For example, in a polymer of methyl methacrylate, the structural unit derived from methyl methacrylate is represented by -CH2-C(CH3)(COOCH3)-.
[0066] It should be noted that, in the case of a polymer of a compound having an ionic functional group and an ethylenically unsaturated bond, for example, a structural unit having an ionic functional group such as a carboxyl group as the second structural unit described later, whether a part of the functional group has been ion-exchanged or not, is regarded as a structural unit derived from the same ionic compound. For example, a structural unit represented by -CH2-C(CH3)(COONa)- can also be regarded as a structural unit derived from methacrylic acid.
[0067] In addition, regarding the compound having multiple independent ethylenically unsaturated bonds, as the structural unit of the polymer of the compound, more than one ethylenically unsaturated bond may remain inside the structural unit. For example, in the case of a polymer of divinylbenzene, the structural unit derived from divinylbenzene may be a structure without ethylenically unsaturated bonds (the portions corresponding to the two ethylenically unsaturated bonds of divinylbenzene are both introduced into the polymer chain), or a structure with one ethylenically unsaturated bond (the portion corresponding to only one ethylenically unsaturated bond is introduced into the polymer chain). Here, the so-called multiple independent ethylenically unsaturated bonds refer to multiple ethylenically unsaturated bonds that do not form conjugated dienes with each other.
[0068] Furthermore, when the functional groups other than the chain structure corresponding to the ethylenically unsaturated bond in the polymer after polymerization, such as the carboxyl group, no longer correspond to the chemical structure of the monomer due to a chemical reaction, the structural unit of the polymer is set to the structural unit derived from the compound having an ethylenically unsaturated bond in the polymer. For example, when vinyl acetate is polymerized and then saponified, it is considered that the structural unit of the polymer is set to the structural unit derived from vinyl alcohol instead of the structural unit derived from vinyl acetate based on the chemical structure of the polymer.
[0069] In the present embodiment, the term "class" added to the compound name refers to a group of compounds including the compound structure, and also includes the compound having a substituent.
[0070] <1. Composite particles (P)>
[0071] The composite particles (P) of the present embodiment can be used as a binder for non-aqueous secondary batteries as a method. The composite particles (P) of the present embodiment include copolymers and thickeners. Regarding the composite particles (P) of the present embodiment, it is presumed that the chain molecules of the copolymer form a particle structure. The shape of the particle structure can be, for example, spherical or substantially spherical, and the molecular weight of the chain molecules can be arbitrarily selected. The composite particles (P) can be particles subjected to emulsion polymerization. The thickener molecules can be present on the surface of the particle structure and on either or both of the inside of the particle structure, and preferably at least a portion of the thickener is present in the particle structure composed of the chain molecules of the copolymer. The reason is that, for example, compared with the case where all the thickeners contained in the composite particles (P) are attached to the outside of the particle structure, if at least a portion of the thickener is present in the particle structure, the interaction between the thickener and the chain molecules is promoted, and the synergistic effect of the copolymer and the thickener is easy to further exert. As a result, a composite particle (P) can be formed that can form an electrode with better adhesion between electrode active materials and between electrode active materials and collectors.
[0072] (Copolymer)
[0073] The copolymer contained in the composite particles (P) of the present embodiment has at least the first structural unit derived from the monomer (a1) shown below and the second structural unit derived from the monomer (a2) shown below.
[0074] The copolymer contained in the composite particles (P) of the present embodiment may contain, in addition to the first structural unit and the second structural unit, a third structural unit derived from a monomer (a3) composed of a compound having multiple independent ethylenically unsaturated bonds which is not equivalent to the monomer (a1) or the monomer (a2), and / or a fourth structural unit derived from another monomer (a4) which is not equivalent to any of the monomers (a1) to (a3).
[0075] [1st structural unit]
[0076] The first structural unit in the copolymer contained in the composite particles (P) of the present embodiment is derived from the monomer (a1).
[0077] Monomer (a1) is a nonionic compound having only one ethylenically unsaturated bond. That is, monomer (a1) is a compound having neither anionic functional groups nor cationic functional groups. However, the silane compound is not included in monomer (a1). Monomer (a1) may be only one compound or a combination of two or more compounds.
[0078] As the monomer (a1), at least one of (meth)acrylate and an aromatic compound having an ethylenically unsaturated bond is preferably used, and a combination of the two compounds is more preferably used. The (meth)acrylate is more preferably an alkyl (meth)acrylate. The number of carbon atoms of the alkyl group in the alkyl (meth)acrylate is preferably 1 to 20. When such a compound is used, the monomer (a1) other than the alkyl (meth)acrylate and the aromatic compound having an ethylenically unsaturated bond described later may be used in combination.
[0079] As the (meth)acrylic acid alkyl ester contained in the example of the (meth)acrylic acid ester used as the monomer (a1), for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isobornyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, etc. In order to form a composite particle (P) that can form an electrode active material layer with excellent electrolyte resistance, it is preferred that 2-ethylhexyl acrylate be included among them.
[0080] As the aromatic compound having an ethylenically unsaturated bond used as the monomer (a1), for example, styrene, tert-butylstyrene, α-methylstyrene, p-methylstyrene, 1,1-diphenylethylene, etc. can be mentioned. When the monomer (a1) contains an aromatic vinyl compound, it is more preferable to contain at least one of styrene and α-methylstyrene. In order to have excellent dispersibility in aqueous media and to have a non-aqueous secondary battery having an electrode containing a binder for a non-aqueous secondary battery containing the composite particles (P) with better cycle characteristics, it is further preferable to contain styrene.
[0081] Examples of the monomer (a1) other than the (meth)acrylate and the aromatic compound having an ethylenically unsaturated bond include a compound having an ethylenically unsaturated bond and a polar functional group, an aliphatic hydrocarbon compound having an ethylenically unsaturated bond, and an alicyclic hydrocarbon compound having an ethylenically unsaturated bond.
[0082] The polar functional group in the compound having an ethylenically unsaturated bond and a polar functional group used as the monomer (a1) preferably contains at least one of a hydroxyl group and a cyano group, and more preferably contains a hydroxyl group.
[0083] Examples of the compound having an ethylenically unsaturated bond and a polar functional group used as the monomer (a1) include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, (meth)acrylonitrile, etc. In order to obtain good polymerization stability when producing the composite particles (P), 2-hydroxyethyl methacrylate is preferably included.
[0084] [Second structural unit]
[0085] The second structural unit in the copolymer contained in the composite particles (P) of the present embodiment is derived from the monomer (a2).
[0086] The monomer (a2) is a compound having only one ethylenically unsaturated bond and at least one carboxyl group. The monomer (a2) may be only one compound or a combination of two or more compounds.
[0087] As the monomer (a2), a compound having two or more carboxyl groups in one molecule can be used. That is, the copolymer may contain a plurality of carboxyl groups in one structural unit.
[0088] Examples of monomers (a2) having a carboxyl group include unsaturated monocarboxylic acids such as methacrylic acid, acrylic acid, and crotonic acid; unsaturated dicarboxylic acids such as itaconic acid and fumaric acid, etc. In order to form composite particles (P) that can form electrodes with good adhesion between electrode active materials and between electrode active materials and collectors, among them, monomer (a2) preferably uses at least one of acrylic acid, methacrylic acid, and itaconic acid.
[0089] At least a portion of the structural unit derived from the monomer (a2) may also form a salt with an alkaline substance. Examples of monomers (a2) that form salts include metal salts and ammonium salts of monomers (a2). Examples of metals of metal salts include alkali metals such as lithium, sodium, and potassium. Specific compounds include lithium (meth)acrylate, lithium itaconate, dilithium itaconate, sodium (meth)acrylate, sodium itaconate, disodium itaconate, ammonium (meth)acrylate, ammonium itaconate, and diammonium itaconate.
[0090] [Third structural unit]
[0091] The copolymer contained in the composite particles (P) of the present embodiment may have a third structural unit as an optional structural unit. The third structural unit is derived from monomer (a3). Monomer (a3) is a compound having two or more independent ethylenically unsaturated bonds. The number of ethylenically unsaturated bonds can be arbitrarily selected, for example, it can be 2 to 10, 3 to 8, or 4 to 6. It should be noted that the so-called "independent" refers to a conjugated double bond that is not possessed by 1,3-butadiene. Therefore, monomer (a3) is a compound that can form a cross-linked structure in free radical polymerization with monomer (a1) and monomer (a2). Monomer (a3) is not equivalent to either monomer (a1) or monomer (a2). As monomer (a3), one compound can be used, or two or more different compounds can be used.
[0092] Examples of the monomer (a3) include compounds having two ethylenically unsaturated bonds such as divinylbenzene, ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and 2-hydroxy-3-acryloyloxypropyl methacrylate, and compounds having three or more ethylenically unsaturated bonds such as trimethylolpropane tri(meth)acrylate. In order to obtain good polymerization stability when producing the composite particles (P), and to obtain a lower internal resistance of a non-aqueous secondary battery having an electrode including a binder for a non-aqueous secondary battery containing the composite particles (P), and to have excellent cycle characteristics, the monomer (a3) preferably uses at least one of divinylbenzene and trimethylolpropane triacrylate.
[0093] [Other monomers (a4)]
[0094] Other monomers (a4) are monomers that are not equivalent to any of monomers (a1) to (a3). Examples of other monomers (a4) include compounds having only one ethylenically unsaturated bond and having anionic functional groups other than carboxyl groups such as sulfonic groups and phosphoric acid groups, surfactants having ethylenically unsaturated bonds (hereinafter sometimes referred to as "polymerizable surfactants"), compounds having ethylenically unsaturated bonds and having a function as a silane coupling agent, etc., but are not limited to these.
[0095] Examples of the compound having only one ethylenically unsaturated bond and having a sulfonic group include aromatic vinyl compounds having a sulfonic group, aromatic vinyl compounds having a sulfonic group in the form of a salt, etc. Among them, at least one of p-styrenesulfonic acid and p-styrenesulfonate is preferably used, and p-styrenesulfonate is more preferably used. In order to obtain good polymerization stability when producing the composite particles (P), sodium p-styrenesulfonate is further preferably used.
[0096] As the polymerizable surfactant which is an example of other monomer (a4), a compound having an ethylenically unsaturated bond and having a function as a surfactant can be used.
[0097] Examples of the polymerizable surfactant include compounds represented by the following chemical formulas (1) to (4).
[0098]
[0099] In formula (1), R 1 is an alkyl group. p is an integer of 10 to 40. 1 An alkyl group having 10 to 40 carbon atoms is preferred, and a linear unsubstituted alkyl group having 10 to 40 carbon atoms is more preferred.
[0100]
[0101] In formula (2), R 2 is an alkyl group. q is an integer of 10 to 12. 2 It is preferably an alkyl group having 10 to 40 carbon atoms, and more preferably a linear unsubstituted alkyl group having 10 to 40 carbon atoms. Examples of the compound represented by formula (4) include polyoxyethylene alkyl ether sulfate (Aqualon KH-10 manufactured by Daiichi Kogyo Seiyaku Co., Ltd.).
[0102]
[0103] In formula (3), R 3 M is an alkyl group. 1 is NH4 or Na. 3 An alkyl group having 10 to 40 carbon atoms is preferred, and a linear unsubstituted alkyl group having 10 to 40 carbon atoms is more preferred.
[0104]
[0105] In formula (4), R 4 M is an alkyl group. 2 is NH4 or Na. 4 An alkyl group having 10 to 40 carbon atoms is preferred, and a linear unsubstituted alkyl group having 10 to 40 carbon atoms is more preferred.
[0106] Examples of the compound having an ethylenically unsaturated bond and functioning as a silane coupling agent as an example of other monomers (a4) include vinyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, and γ-methacryloxypropyltriethoxysilane.
[0107] [Content ratio of each structural unit in the copolymer]
[0108] The content of each structural unit in the copolymer contained in the composite particles (P) of the present embodiment is regarded as being the same as the content of each monomer in the total amount of the monomer components used when producing the composite particles (P).
[0109] (Content ratio of the first structural unit in all structural units)
[0110] The content of the first structural unit in all structural units of the copolymer (in other words, the content of the monomer (a1) in the total amount of the monomer components used when manufacturing the composite particles (P)) is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 75% by mass or more, and particularly preferably 80% by mass or more. This is because better polymerization stability can be obtained when manufacturing the composite particles (P). The content of the first structural unit in all structural units is preferably 97% by mass or less, more preferably 95% by mass or less, and further preferably 94% by mass or less. This is because it is a composite particle (P) that can form an electrode with good bonding between electrode active materials and between electrode active materials and collectors.
[0111] Regarding the composition of the monomer (a1), it is preferred to appropriately adjust the type and amount of the compound in order to adjust the glass transition point of the composite particles (P) or to adjust the polymerization rate in accordance with the molecular design.
[0112] Specifically, when the monomer (a1) contains an aromatic compound having an ethylenically unsaturated bond, the content of the structural unit derived from the aromatic compound having an ethylenically unsaturated bond in all structural units is preferably 36% by mass or more, more preferably 41% by mass or more, and further preferably 43% by mass or more. This is because it becomes a composite particle (P) with excellent dispersibility when manufacturing a binder composition for a non-aqueous secondary battery containing the composite particle (P).
[0113] (Content ratio of the second structural unit in all structural units)
[0114] The content of the second structural unit in all structural units of the copolymer (in other words, the content of the monomer (a2) in the total amount of the monomer components used when manufacturing the composite particles (P)) is preferably 0.10% by mass or more, more preferably 1.0% by mass or more, further preferably 3.0% by mass, and particularly preferably 4.0% by mass or more. This is because it becomes a composite particle (P) that can form an electrode with better adhesion between the electrode active material and between the electrode active material and the collector. The content of the second structural unit in all structural units is preferably 20% by mass or less, more preferably 15% by mass or less, and further preferably 10% by mass or less. This is because better polymerization stability is obtained when manufacturing the composite particles (P).
[0115] (Content ratio of the third structural unit in all structural units)
[0116] In the case where the copolymer contained in the composite particles (P) of the present embodiment includes the third structural unit, the content of the third structural unit in all the structural units of the copolymer (in other words, the content of the monomer (a3) in the total amount of the monomer components used when manufacturing the composite particles (P)) is preferably 0.010% by mass or more, more preferably 0.020% by mass or more, and further preferably 0.030% by mass or more. This is because the effect of monomer (a3) as an internal crosslinking agent can be significantly obtained, the degradation of the copolymer is suppressed, and the composite particles (P) can be used as a material for a binder of a non-aqueous secondary battery that can obtain better cycle characteristics. The content of the third structural unit in all the structural units of the copolymer is preferably 10% by mass or less, more preferably 5.0% by mass or less, further preferably 1.0% by mass or less, and particularly preferably 0.1% by mass or less. This is because the gelation of the copolymer can be suppressed.
[0117] (Content ratio of the fourth structural unit in all structural units)
[0118] In the case where the copolymer contained in the composite particles (P) of the present embodiment includes the 4th structural unit derived from other monomers (a4), and the other monomers (a4) are compounds having only one ethylenically unsaturated bond and having a sulfonic group, the content of the 4th structural unit in all structural units of the copolymer (in other words, the content of the monomer (a4) in the total amount of the monomer components used when manufacturing the composite particles (P)) is preferably 0.10% by mass or more, more preferably 0.20% by mass or more, and further preferably 0.30% by mass or more. This is because good polymerization stability can be obtained when manufacturing the composite particles (P). The content of the 4th structural unit in all structural units of the copolymer is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, and further preferably 1.0% by mass or less. This is because the particle size, viscosity, etc. of the composite particles (P) can be appropriately adjusted.
[0119] In the case where the copolymer of the present embodiment includes the 4th structural unit derived from other monomers (a4) and other monomers (a4) are polymerizable surfactants, the content of the 4th structural unit in all structural units of the copolymer (in other words, the content of the monomer (a4) in the total amount of monomer components used when manufacturing composite particles (P)) is preferably 0.10 mass % or more, more preferably 0.20 mass % or more, and further preferably 0.30 mass % or more. This is because the effect brought about by the inclusion of a polymerizable surfactant becomes significant, and good polymerization stability can be obtained when manufacturing composite particles (P). The content of the 4th structural unit in all structural units of the copolymer is preferably 5.0 mass % or less, more preferably 3.0 mass % or less, and further preferably 1.0 mass % or less. This is because the particle size, viscosity, etc. of the composite particles (P) can be appropriately adjusted.
[0120] (Thickener)
[0121] The type of thickener contained in the composite particles (P) of the present embodiment is not particularly limited as long as the effect of the present invention is not inhibited. The thickener may be used alone or in combination of two or more.
[0122] As the tackifier, for example, natural resins such as rosin resins and terpene resins; petroleum resins such as hydrogenated petroleum resins and unhydrogenated petroleum resins can be cited. In order to have excellent compatibility with the copolymer in the composite particles of this embodiment, it is preferably at least one selected from rosin resins, terpene resins, and hydrogenated petroleum resins, and more preferably at least one selected from terpene resins and hydrogenated petroleum resins.
[0123] Examples of the rosin-based resin include rosin resins such as gum rosin, tall oil rosin, and wood rosin; modified rosin resins such as hydrogenated rosin resin, disproportionated rosin resin, and polymerized rosin resin; and rosin ester resins such as glycerol esters and pentaerythritol esters of these rosin resins and modified rosin resins. The rosin-based resin may be in the form of an emulsion obtained by emulsifying these.
[0124] Examples of the terpene resin include terpene resins containing α-pinene, β-pinene, dipentene, etc. as main components, aromatic modified terpene resins, hydrogenated terpene resins, terpene phenol resins, etc. The terpene resin may be in the form of an emulsion obtained by emulsifying these.
[0125] As the petroleum resin, hydrogenated petroleum resin (hereinafter also referred to as "hydrogenated petroleum resin") can be used, and unhydrogenated petroleum resin can also be used. In order to have good compatibility with the copolymer, it is preferred to use hydrogenated petroleum resin. As petroleum resin, for example, aliphatic (C5 series) petroleum resin, aromatic (C9 series) petroleum resin, copolymer (C5 / C9 series) petroleum resin, dicyclopentadiene series petroleum resin, alicyclic saturated hydrocarbon resin, etc. can be cited. The substance obtained by hydrogenating at least a part of the unsaturated groups present in these resins is hydrogenated petroleum resin. In addition, the petroleum resin can also be in the form of an emulsion obtained by emulsifying them. In order to form a composite particle (P) that can form an electrode with better adhesion between electrode active materials and between electrode active materials and collectors, alicyclic saturated hydrocarbon resins are preferred among these petroleum resins.
[0126] The softening point of the thickener is not particularly limited. For example, the softening point of the thickener is preferably 25 to 200°C, more preferably 25 to 175°C, and further preferably 25 to 150°C. It may also be 35 to 130°C, 50 to 100°C, 60 to 80°C, etc. If the softening point of the thickener is above 25°C, the compatibility with the copolymer is improved, so it is preferred. If the softening point of the thickener is below 200°C, it becomes a composite particle (P) that can form an electrode with better adhesion between the electrode active material and between the electrode active material and the collector. As a result, a non-aqueous secondary battery having an electrode using it exhibits better cycle characteristics.
[0127] The softening point of the thickener is preferably 70 to 140° C., more preferably 80 to 140° C., further preferably 85 to 135° C., and particularly preferably 90 to 130° C., when the thickener is a hydrogenated petroleum resin. If the softening point of the hydrogenated petroleum resin is 70° C. or higher, the compatibility with the copolymer is improved, so it is preferred. If the softening point of the hydrogenated petroleum resin is 140° C. or lower, it becomes a composite particle (P) that can form an electrode with better bonding between electrode active materials and between electrode active materials and collectors.
[0128] The softening point of the tackifier is a value measured using a ring and ball softening point measuring device based on JIS K6220-1:2001.
[0129] [Content of thickener in composite particles (P)]
[0130] The content of the thickener relative to the amount of the copolymer in the composite particles (P) of the present embodiment is regarded as being the same as the mass of the thickener relative to the total mass of the monomer components used when producing the composite particles (P).
[0131] Relative to 100 parts by mass of the monomer component used in the manufacture of the copolymer in the composite particle (P) of the present embodiment, the content of the thickener is preferably 0.50 to 20 parts by mass, more preferably 0.70 to 18 parts by mass, and further preferably 1.0 to 15 parts by mass. It can also be 1.5 to 10 parts by mass, 2.0 to 8.0 parts by mass, 3.0 to 6.0 parts by mass, etc. If the content of the thickener is 0.50 parts by mass or more, the effect brought about by the composite particle (P) containing the thickener becomes significant. As a result, a composite particle (P) is formed that can form an electrode with better adhesion between the electrode active material and between the electrode active material and the collector. If the content of the thickener is 20 parts by mass or less, the content of the copolymer in the composite particle (P) can be fully ensured, and the internal resistance of the non-aqueous secondary battery having an electrode containing a binder for a non-aqueous secondary battery containing the composite particle (P) is lower.
[0132] [Glass transition temperature (Tg) of composite particles (P)]
[0133] The glass transition temperature (Tg) of the composite particles (P) of the present embodiment is the peak top temperature of a DDSC chart obtained by temperature differential of DSC by DSC measurement at a heating rate of 10°C / min in a nitrogen atmosphere using a differential scanning calorimetry (DSC) apparatus (EXSTARDSC / SS7020 manufactured by Hitachi High-Tech Science & Technology Co., Ltd.).
[0134] The glass transition temperature (Tg) of the composite particles (P) is preferably -30°C or higher, more preferably -20°C or higher, and further preferably -10°C or higher. This is because a nonaqueous secondary battery having an electrode containing the binder for a nonaqueous secondary battery containing the composite particles (P) has excellent cycle characteristics.
[0135] The glass transition temperature (Tg) of the composite particles (P) is preferably 100°C or less, more preferably 50°C or less, and further preferably 40°C or less. This is because the film-forming property of the composite particles (P) is improved, and the non-aqueous secondary battery having an electrode comprising a binder for a non-aqueous secondary battery containing the composite particles (P) has excellent cycle characteristics. The glass transition temperature (Tg) of the composite particles (P) may be, for example, -20°C or more and 60°C or less, -5°C or more and 30°C or less, 0°C or more and 25°C or less, 5°C or more and 20°C or less, etc., as required.
[0136] [Method for producing composite particles (P)]
[0137] The composite particles (P) of the present embodiment can be produced, for example, by the method described below.
[0138] It can be produced by copolymerizing (polymerization process) raw material monomers including monomer (a1) and monomer (a2), and as required, monomer (a3) composed of a compound having multiple independent ethylenically unsaturated bonds and / or other monomers (a4) in the presence of a thickener. Hereinafter, the monomers ((a1) to (a4) components) used to synthesize the composite particles (P) are sometimes collectively referred to as raw material monomers (a). The raw material monomer (a) can be a mixture including monomer (a1) and monomer (a2), and as required, further including monomer (a3) and / or monomer (a4). In the method for producing the composite particles (P), before the copolymerization process, there can also be a process of adding the monomers and the thickener to the aqueous medium.
[0139] As a method for copolymerizing the raw monomer (a) in the presence of a thickener, for example, an emulsion polymerization method in which the raw monomer (a) is subjected to emulsion polymerization in an aqueous medium (b) containing a thickener can be cited. In the case of manufacturing composite particles (P) by emulsion polymerization, in addition to the thickener, the raw monomer (a) and the aqueous medium (b), components such as a non-polymerizable surfactant (c), an alkaline substance (d), a free radical polymerization initiator (e), and / or a chain transfer agent (f) can also be used as required. If a specific example is cited, a mixture containing a thickener, a raw monomer (a) and an aqueous medium (b) can be cited, and the mixture and the free radical polymerization initiator (e) are each continuously supplied to an aqueous medium (b) prepared separately, and a method for copolymerization can be cited.
[0140] [Aqueous medium (b)]
[0141] The aqueous medium (b) is one selected from water, a hydrophilic solvent, and a mixture containing water and a hydrophilic solvent. As the hydrophilic solvent, methanol, ethanol, isopropanol and N-methylpyrrolidone can be mentioned. From the viewpoint of polymerization stability, the aqueous medium (b) is preferably water. As the aqueous medium (b), a mixture obtained by adding a hydrophilic solvent to water can be used as long as the polymerization stability is not impaired.
[0142] [Non-polymerizable surfactant (c)]
[0143] When composite particles (P) are manufactured by emulsion polymerization, a non-polymerizable surfactant (c) can be contained in a solution containing a thickener, an aqueous medium (b) and a raw monomer (a) to carry out emulsion polymerization. The so-called non-polymerizable surfactant (c) is a surfactant (c) that does not have a polymerizable unsaturated bond in its chemical structure. The surfactant (c) improves the dispersion stability of the solution in the emulsion polymerization and / or the dispersion (emulsion) obtained after the polymerization. As a preferred surfactant (c), an anionic surfactant can be used, and a nonionic surfactant can also be used.
[0144] Examples of the anionic surfactant include alkylbenzene sulfonates, alkyl sulfate ester salts, polyoxyethylene alkyl ether sulfate ester salts, and fatty acid salts.
[0145] Examples of the nonionic surfactant include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene polycyclic phenyl ethers, polyoxyalkylene alkyl ethers, sorbitan fatty acid esters, and polyoxyethylene sorbitan fatty acid esters.
[0146] The above-mentioned surfactant (c) may be used alone or in combination of two or more.
[0147] [Alkaline substances (d)]
[0148] In the case of manufacturing composite particles (P) by emulsion polymerization, an alkaline substance (d) may also be added to the solution before emulsion polymerization and / or the dispersion after emulsion polymerization containing a thickener, an aqueous medium (b) and a raw material monomer (a). The alkaline substance (d) may also be added to the dispersion in the emulsion polymerization. By adding the alkaline substance (d), the acidic components contained in the raw material monomer (a) are neutralized. As a result, the pH of the solution in the emulsion polymerization and / or the dispersion after the emulsion polymerization becomes a suitable range, and the stability of the solution in the emulsion polymerization and / or the dispersion after the emulsion polymerization becomes good.
[0149] Examples of the alkaline substance (d) that can be added to the solution before emulsion polymerization and / or the dispersion after emulsion polymerization include ammonia, triethylamine, sodium hydroxide, lithium hydroxide, etc. These alkaline substances (d) may be used alone or in combination of two or more.
[0150] [Free radical polymerization initiator (e)]
[0151] The free radical polymerization initiator (e) used when preparing the composite particles (P) by emulsion polymerization is not particularly limited, and known substances can be used. Examples of the free radical polymerization initiator (e) include persulfates such as ammonium persulfate and potassium persulfate; hydrogen peroxide; azo compounds; organic peroxides such as tert-butyl hydroperoxide, tert-butyl peroxybenzoate, and cumene hydroperoxide. The free radical polymerization initiator (e) can also be used in the form of an aqueous solution.
[0152] In the present embodiment, when the composite particles (P) are produced by emulsion polymerization, a reducing agent such as sodium hydrogen sulfite, Rongalite, or ascorbic acid may be used together with the radical polymerization initiator (e) to carry out redox polymerization.
[0153] The amount of the radical polymerization initiator (e) added (including the reducing agent in the case of using the reducing agent in combination) is preferably 0.001 parts by mass or more relative to 100 parts by mass of the raw material monomer (a), and more preferably 0.002 parts by mass or more. This is because when the composite particles (P) are manufactured by emulsion polymerization, the conversion rate of the raw material monomer (a) to the composite particles (P) can be increased. The amount of the radical polymerization initiator (e) added is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less relative to 100 parts by mass of the raw material monomer (a). This is because the molecular weight of the copolymer contained in the composite particles (P) can be increased, and the swelling rate of the non-aqueous secondary battery electrode containing the composite particles (P) of the present embodiment to the electrolyte can be reduced. The amount of the radical polymerization initiator (e) added can be 0.1 parts by mass or more and 7.0 parts by mass or less, can be 0.5 parts by mass or more and 3.0 parts by mass or less, can also be 1.0 parts by mass or more and 2.0 parts by mass or less, but is not limited to these.
[0154] [Chain transfer agent (f)]
[0155] The chain transfer agent (f) preferably used when preparing the composite particles (P) by emulsion polymerization is used to adjust the molecular weight of the copolymer forming the composite particles (P) obtained by emulsion polymerization. Examples of the chain transfer agent (f) include n-dodecyl mercaptan, tert-dodecyl mercaptan, n-butyl mercaptan, 2-ethylhexyl thioglycolate, 2-mercaptoethanol, β-mercaptopropionic acid, methanol, n-propanol, isopropanol, tert-butyl alcohol, benzyl alcohol, and the like.
[0156] [Emulsion polymerization method]
[0157] As the emulsion polymerization method used in the manufacture of composite particles (P), for example, there can be mentioned a method in which each component used for emulsion polymerization is continuously supplied to a reaction container while carrying out emulsion polymerization. An aqueous medium such as water may also be added to the reaction container in advance. The temperature of the emulsion polymerization is not particularly limited, and is, for example, 30 to 90°C, preferably 50 to 85°C, and more preferably 55 to 80°C. The emulsion polymerization is preferably carried out while stirring. In addition, it is preferred that the raw material monomer (a), the thickener and the free radical polymerization initiator (e) are continuously supplied to the solution in the emulsion polymerization in such a manner that the concentrations of the raw material monomer (a), the thickener and the free radical polymerization initiator (e) in the solution in the emulsion polymerization become uniform.
[0158] Here, an example of a composition containing composite particles (P) obtained by the production method of the present embodiment and an aqueous medium will be described with reference to the drawings.
[0159] Figure 1 Schematic diagram for explaining the state of a composition including composite particles (P) obtained by the production method of this embodiment and an aqueous medium existing around the composite particles (P). Figure 1 The composite particles 10 shown are particles produced using the production method of this embodiment having a polymerization step of copolymerizing a raw material monomer (a) containing a monomer (a1) and a monomer (a2) in the presence of a thickener 2. The composite particles 10 are dispersed in an aqueous medium.
[0160] Figure 1 The composite particles 10 shown include copolymer 1 and thickener 2. Figure 1 When the composition including the composite particles 10 and the aqueous medium shown forms an electrode, the synergistic effect brought by the copolymer 1 and the thickener 2 contained in the composite particles 10 between the electrode active materials and the composite particles 10 between the electrode active materials and the current collector is fully exerted. Therefore, the electrode has good adhesion between the electrode active materials and the adhesion between the electrode active materials and the current collector. As a result, a non-aqueous secondary battery and a non-aqueous secondary battery electrode with excellent cycle characteristics can be obtained.
[0161] about Figure 1 The copolymer 1 contained in the composite particle 10 shown is, as one way of speculation by the inventors, Figure 1 As shown in FIG. 1 , the thickener 2 has a particle-like shape and is integrated with the particle-like structure 3 composed of randomly coiled polymer chains, i.e., chain molecules. As one embodiment of the inventor's speculation, the thickener 2 has a particle-like shape and is integrated with the particle-like structure 3 composed of chain molecules. In more detail, Figure 1As shown, the thickener 2 contained in the composite particle 10 is considered to be in a state of being incorporated into the particulate structure 3 composed of the chain molecules of the copolymer 1. The thickener 2 present in the particulate structure 3 is formed by the thickener 2 being surrounded by the chain molecules of the copolymer 1 during the process in which the raw material monomer (a) in a mixed state with the thickener 2 becomes the copolymer 1 in the above-mentioned polymerization step.
[0162] The thickener 2 contained in the composite particles 10 may be Figure 1 As shown in the figure, all of the thickener 2 is present in the particulate structure 3, and a part of it may be attached to the outside of the particulate structure 3. The content of the thickener 2 contained in the composite particle 10 and the number of particles composed of the thickener 2 are not particularly limited, and the size of the composite particle 10 can be changed according to the amount of the thickener 2 used relative to the amount of the raw material monomer (a) used in the manufacture of the composite particle 10, and can be appropriately determined according to the purpose. The size of the composite particle 10 can also be arbitrarily selected.
[0163] As a way, Figure 1 The composite particles 10 shown are emulsified particles (dispersed particles) containing a copolymer 1, a thickener 2, and a surfactant 4. Specifically, Figure 1 The composite particle 10 shown has a surfactant 4 bonded with the hydrophilic group facing outward in the copolymer 1 forming the outer surface of the particle-like structure 3. The surfactant 4 is not equivalent to the raw material monomer (a) containing the polymerizable surfactant as other monomers (a4) used when manufacturing the composite particle 10, but is derived from a non-polymerizable surfactant (c).
[0164] The composite particles (P) of this embodiment only need to contain the copolymer 1 and the thickener 2, and can be Figure 1 As shown in the figure, the composite particle 10 has a surfactant 4, and it can also be as Figure 2 As shown, the composite particles 11 do not contain a surfactant.
[0165] Figure 2 This is a schematic diagram for explaining the state of a composition including other composite particles 11 different from the composite particles 10 obtained by the production method of this embodiment and an aqueous medium located around the composite particles 11 . Figure 2The composite particles 11 shown are soap-free emulsions without surfactants, dispersed in an aqueous medium. The composition containing the composite particles 11 without surfactants can be manufactured, for example, by using a soap-free emulsion polymerization method. If a specific example is given, the composition can be manufactured using the following soap-free emulsion polymerization method: when manufacturing the composite particles 11, a water-soluble polymer having a functional group such as a carboxyl group is used instead of a surfactant; or, as the raw material monomer (a), a polymerizable surfactant having free radical polymerizability is used, and a method of copolymerizing the raw material monomer (a) in the presence of a thickener 2 is used.
[0166] In use Figure 2 When the composition comprising the composite particles 11 and the aqueous medium forms an electrode, it is also similar to the case where the electrode is formed by using Figure 1 In the case of the composition including the composite particles 10 and the aqueous medium shown, the composite particles 11 present between the electrode active materials and the composite particles 11 present between the electrode active materials and the current collector contain the copolymer 1 and the thickener 2. Therefore, the synergistic effect brought about by the copolymer 1 and the thickener 2 is fully exerted, and the electrode active materials and the electrode active materials are formed to have good bonding properties.
[0167] On the other hand, when an electrode is formed using a binder composed of a composition in which the copolymerization of the raw material monomer (a) is not carried out in the presence of the thickener 2, the binding property between the electrode active materials and the binding property between the electrode active materials and the current collector cannot be sufficiently obtained as shown below. Figure 1 The composite particles 10 shown are obtained by dispersing a copolymer produced in the same manner and a separately added thickener 2 in an aqueous medium in the presence of a surfactant 4 .
[0168] Figure 3 For the purpose of explaining the copolymerization of the raw material monomer (a) without using the thickener 2 Figure 1 The composite particle 10 shown is a schematic diagram showing the state of a composition of a copolymer particle 20 made of the copolymer 1 and a thickener 2 added separately, which is produced in the same manner as the composite particle 10 . Figure 3 The copolymer particles 20 shown are emulsified particles containing copolymer 1 and surfactant 4. The emulsified particles do not contain thickener 2. Thickener 2 is combined with surfactant 42 to form another emulsified particle. Figure 3In the composition shown, copolymer particles 20 containing copolymer 1 exist separately from thickener 2 in an aqueous medium. Therefore, copolymer 1 and thickener 2 are easily arranged in a separated state between electrode active materials forming an electrode and between electrode active materials and current collectors. As a result, the synergistic effect brought about by copolymer 1 and thickener 2 cannot be fully obtained, and the electrode has insufficient bonding between electrode active materials and between electrode active materials and current collectors.
[0169] and, Figure 3 In the composition shown, in addition to the surfactant 4 used when manufacturing the copolymer 1, a surfactant 42 for dispersing the thickener 2 in the aqueous medium is also included. Therefore, compared with the composition containing the composite particles of the present embodiment, the content of the surfactant contained in the composition is more, and the possibility of residual surfactant as an impurity in the electrode is higher. As a result, the cycle characteristics of the battery equipped with the electrode are adversely affected, which becomes the reason for reducing the cycle characteristics of the battery. Therefore, it is preferred not to use the surfactant 42 for dispersing the thickener 2. However, from the perspective of the operating environment when manufacturing the electrode, it is preferred to use an aqueous medium as a solvent, but in order to disperse the thickener 2 in the aqueous medium, a surfactant 42 has to be used.
[0170] For these reasons, in the use Figure 3 When the electrode is formed from the composition shown above, a non-aqueous secondary battery having excellent cycle characteristics cannot be obtained.
[0171] <2. Binders for non-aqueous secondary batteries>
[0172] The non-aqueous secondary battery binder of the present embodiment includes the composite particles (P) of the present embodiment. The electrode binder for non-aqueous secondary batteries may also include other components while including the composite particles (P). Specifically, the electrode binder for non-aqueous secondary batteries may also include, for example, polymers, surfactants, etc. other than the composite particles (P).
[0173] The binder for non-aqueous secondary batteries is composed of components that do not volatilize and remain even if a heating process is performed in the manufacturing method of the non-aqueous secondary battery described later. Specifically, for example, the components constituting the binder for non-aqueous secondary batteries are the following components: 1 g of a binder composition for non-aqueous secondary batteries containing composite particles (P) is weighed, placed on an aluminum dish with a diameter of 5 cm and placed in a dryer, and the components that remain after drying for 1 hour at an air pressure (1013 hPa) and a temperature of 105°C while circulating the air in the dryer.
[0174] The content of the composite particles (P) in the binder for non-aqueous secondary batteries is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and further preferably 98% by mass or more. This is because the effect brought about by the inclusion of the composite particles (P) becomes significant.
[0175] <3. Binder composition for non-aqueous secondary batteries>
[0176] The binder composition for non-aqueous secondary batteries of this embodiment comprises the composite particles (P) of this embodiment and an aqueous medium (B). In the binder composition for non-aqueous secondary batteries of this embodiment, the composite particles (P) are preferably dispersed in the aqueous medium (B) in an emulsion state.
[0177] The binder composition for non-aqueous secondary batteries may contain other components in addition to the composite particles (P) and the aqueous medium (B). Specifically, the binder composition for non-aqueous secondary batteries may contain, for example, the above-mentioned components used in the synthesis of the composite particles (P).
[0178] The binder composition for non-aqueous secondary batteries of the present embodiment may also be a dispersion obtained by manufacturing composite particles (P) by emulsion polymerization. That is, the binder composition for non-aqueous secondary batteries may also be an emulsion comprising composite particles (P) and an aqueous medium (B). In addition, the binder composition for non-aqueous secondary batteries of the present embodiment may also be a dispersion obtained by dispersing composite particles (P) obtained by a method other than emulsion polymerization in an aqueous medium (B). In this case, as a method for dispersing composite particles (P) in an aqueous medium (B), a known method can be used.
[0179] 〔Aqueous medium (B)〕
[0180] The aqueous medium (B) in the binder composition for non-aqueous secondary batteries of the present embodiment is water, a hydrophilic solvent or a mixture thereof. As an example of a hydrophilic solvent, the same substance as the hydrophilic solvent exemplified as the aqueous medium (b) used in the synthesis of the composite particles (P) can be cited. The aqueous medium (B) may be the same as or different from the aqueous medium (b) used in the synthesis of the composite particles (P).
[0181] In the case where the binder composition for non-aqueous secondary batteries is an emulsion obtained by manufacturing composite particles (P) using an emulsion polymerization method, the aqueous medium (B) may be an aqueous medium (b) used for the synthesis of composite particles (P). In addition, the aqueous medium (B) may also be a substance obtained by adding a new aqueous medium to the aqueous medium (b) used for the synthesis of composite particles (P). In addition, the aqueous medium (B) may also be a substance in which a part or all of the aqueous medium (b) contained in the dispersion obtained by manufacturing composite particles (P) using an emulsion polymerization method is replaced with a new aqueous solvent. The new aqueous medium used in this case may be the same composition as the aqueous medium (b) used for the synthesis of composite particles (P), or may be a different composition.
[0182] [Non-volatile content concentration of the binder composition for non-aqueous secondary batteries]
[0183] The non-volatile component concentration of the non-aqueous secondary battery binder composition of the present embodiment is preferably 20% by mass or more, more preferably 25% by mass or more, and further preferably 30% by mass or more. This is because the amount of active ingredients contained in the non-aqueous secondary battery binder composition is large. The non-volatile component concentration of the non-aqueous secondary battery binder composition can be adjusted by the content of the aqueous medium (B) contained in the non-aqueous secondary battery binder composition.
[0184] The non-volatile content of the binder composition for non-aqueous secondary batteries is preferably 80% by mass or less, more preferably 70% by mass or less, and further preferably 60% by mass or less. This is to suppress the increase in viscosity of the binder composition for non-aqueous secondary batteries and facilitate the preparation of slurry for non-aqueous secondary battery electrodes.
[0185] <4. Slurry for non-aqueous secondary battery electrodes>
[0186] Next, the non-aqueous secondary battery electrode slurry of the present embodiment is described in detail. The non-aqueous secondary battery electrode slurry comprises the composite particles (P) of the present embodiment, an electrode active material and an aqueous medium. Preferably, the composite particles (P) and the electrode active material contained in the non-aqueous secondary battery electrode slurry are dispersed in an aqueous medium. In addition to containing the composite particles (P), the electrode active material and the aqueous medium, the non-aqueous secondary battery electrode slurry may also contain a thickener, a conductive aid, the above-mentioned components used for the synthesis of the composite particles (P), etc.
[0187] [Content of composite particles (P)]
[0188] The content of the composite particles (P) in the nonaqueous secondary battery electrode slurry is preferably 0.50 parts by mass or more, more preferably 1.0 parts by mass or more, based on 100 parts by mass of the electrode active material, because the effects of the inclusion of the composite particles (P) are fully exhibited.
[0189] The content of the composite particles (P) contained in the slurry for non-aqueous secondary battery electrodes is preferably 5.0 parts by mass or less, more preferably 4.0 parts by mass or less, and further preferably 3.0 parts by mass or less relative to 100 parts by mass of the electrode active material. This is because the content of the electrode active material contained in the slurry for non-aqueous secondary battery electrodes can be increased.
[0190] 〔Electrode active material〕
[0191] The electrode active material contained in the slurry for non-aqueous secondary battery electrodes is a material capable of intercalating / deintercalating ions such as lithium ions as charge carriers. The ions as charge carriers are preferably alkali metal ions, more preferably lithium ions, sodium ions, potassium ions, and even more preferably lithium ions.
[0192] In the case where the non-aqueous secondary battery electrode manufactured using the non-aqueous secondary battery electrode slurry is the negative electrode, the electrode active material is the negative electrode active material. As the negative electrode active material, it is preferred to include at least one of a carbon material, a silicon-containing material, and a titanium-containing material. As carbon materials that can be used as negative electrode active materials, for example, cokes such as petroleum coke, asphalt coke, coal coke, carbides of organic polymers, graphites such as artificial graphite and natural graphite can be cited. As silicon-containing materials that can be used as negative electrode active materials, for example, silicon compounds such as silicon simple substance and silicon oxide can be cited. As titanium-containing materials that can be used as negative electrode active materials, for example, lithium titanate can be cited. These materials that can be used as negative electrode active materials can be used alone or in a mixed or composite form.
[0193] The negative electrode active material preferably contains at least one of a carbon material and a silicon-containing material, and more preferably contains a carbon material. This is because the composite particles (P) contained in the non-aqueous secondary battery electrode slurry have a great effect of improving the bonding between the negative electrode active materials and between the negative electrode active materials and the current collector.
[0194] In the case where the non-aqueous secondary battery electrode manufactured using the non-aqueous secondary battery electrode slurry is the positive electrode, the electrode active material is the positive electrode active material. As the positive electrode active material, a material having a higher standard electrode potential than the negative electrode active material is used. Specifically, as the positive electrode active material, nickel-containing lithium composite oxides such as lithium composite oxides of Ni-Co-Mn system, lithium composite oxides of Ni-Mn-Al system, and lithium composite oxides of Ni-Co-Al system, lithium cobalt oxide (LiCoO2), spinel lithium manganese oxide (LiMn2O4), olivine type lithium iron phosphate, TiS2, MnO2, MoO3, V2O5 and other chalcogen compounds can be cited. These materials that can be used as positive electrode active materials can be used alone or in combination of two or more.
[0195] 〔Aqueous medium〕
[0196] The aqueous medium contained in the slurry for non-aqueous secondary battery electrodes of the present embodiment is one selected from water, a hydrophilic solvent and a mixture comprising water and a hydrophilic solvent. As a hydrophilic solvent, the same substance as the hydrophilic solvent exemplified by the aqueous medium (b) used in the synthesis of the composite particles (P) can be cited. The aqueous medium contained in the slurry for non-aqueous secondary battery electrodes may be the same as the aqueous medium (b) used in the synthesis of the composite particles (P) or may be different.
[0197] 〔Thickener〕
[0198] As thickeners that can be included in the non-aqueous secondary battery electrode slurry, celluloses such as carboxymethyl cellulose (CMC), hydroxyethyl cellulose, hydroxypropyl cellulose, ammonium salts of celluloses, alkali metal salts of celluloses, polyvinyl alcohol, polyvinyl pyrrolidone, etc. can be cited. The thickener preferably includes at least one of carboxymethyl cellulose, ammonium salts of carboxymethyl cellulose, and alkali metal salts of carboxymethyl cellulose. This is because the electrode active material in the non-aqueous secondary battery electrode slurry becomes easy to disperse.
[0199] The content of the thickener contained in the non-aqueous secondary battery electrode slurry is preferably 0.50 parts by mass or more, and more preferably 0.80 parts by mass or more, relative to 100 parts by mass of the electrode active material. This is because the adhesion between the electrode active material contained in the non-aqueous secondary battery electrode made using the non-aqueous secondary battery electrode slurry and between the electrode active material and the collector becomes good. The content of the thickener contained in the non-aqueous secondary battery electrode slurry is preferably 3.0 parts by mass or less, more preferably 2.0 parts by mass or less, and further preferably 1.5 parts by mass or less, relative to 100 parts by mass of the electrode active material. This is because the coating property of the non-aqueous secondary battery electrode slurry becomes good.
[0200] 〔Conductive additive〕
[0201] As the conductive aid that can be included in the non-aqueous secondary battery electrode slurry of the present embodiment, carbon black, carbon fiber, etc. can be cited. As carbon black, furnace black, acetylene black, DENKA BLACK (registered trademark) (DENKA Co., Ltd.), CHECKEN BLACK (registered trademark) (CHECKEN BLACK INTARSIONAL Co., Ltd.), etc. can be cited. As carbon fiber, carbon nanotubes, carbon nanofibers, etc. can be cited. As carbon nanotubes, VGCF (registered trademark, Showa Denko Co., Ltd.) as vapor-grown carbon fiber can be cited as a preferred example.
[0202] [Method for producing slurry for non-aqueous secondary battery electrodes]
[0203] As a method for manufacturing the slurry for non-aqueous secondary battery electrodes of the present embodiment, for example, a method of mixing the composite particles (P) of the present embodiment, an electrode active material, an aqueous medium, a thickener contained as needed, a conductive aid contained as needed, and other components contained as needed can be cited. The binder composition of the present embodiment can also be used for slurry manufacturing instead of the composite particles (P) of the present embodiment. The mixing order of the various components of the slurry for non-aqueous secondary battery electrodes as raw materials is not particularly limited and can be appropriately determined. As a method for mixing the various components, a method using a mixing device such as a stirring type, a rotating type, and an oscillating type can be cited.
[0204] <5. Non-aqueous secondary battery electrodes>
[0205] Next, the non-aqueous secondary battery electrode of the present embodiment is described in detail. The electrode of the present embodiment includes the composite particles (P) of the present embodiment. The electrode of the present embodiment includes a current collector and an electrode active material layer formed on the current collector. As the shape of the electrode of the present embodiment, for example, a laminate, a winding body, etc. can be cited, without particular limitation.
[0206] The formation range of the electrode active material layer on the current collector is not particularly limited, and the electrode active material layer can be formed on all surfaces of the current collector, or on only a portion of the current collector. When the current collector is in the shape of a plate, foil, etc., the electrode active material layer can be formed on both sides of the current collector, or only on one side.
[0207] 〔Current Collector〕
[0208] The current collector is preferably a metal sheet having a thickness of 0.001 mm or more and 0.5 mm or less. Examples of the metal forming the metal sheet include iron, copper, aluminum, nickel, stainless steel, etc. When the electrode of this embodiment is a negative electrode of a lithium ion secondary battery, the current collector is preferably a copper foil.
[0209] [Electrode active material layer]
[0210] The electrode active material layer comprises the composite particles (P) of the present embodiment and the electrode active material. The electrode active material layer may also comprise a conductive aid, a thickener, etc. The electrode active material, the conductive aid, and the thickener may all be the same substances as those exemplified as components of the slurry for non-aqueous secondary battery electrodes.
[0211] [Method for producing non-aqueous secondary battery electrode]
[0212] The electrode of the present embodiment can be manufactured, for example, by the method shown below. First, the non-aqueous secondary battery electrode slurry of the present embodiment is applied to the collector. Then, the non-aqueous secondary battery electrode slurry is dried. Thus, an electrode active material layer containing composite particles (P) is formed on the collector to prepare an electrode sheet. Then, the electrode sheet is cut into an appropriate size as needed. By performing the above steps, the electrode of the present embodiment can be obtained.
[0213] As a method for coating the non-aqueous secondary battery electrode slurry on the collector, there is no particular limitation, and for example, reverse roll method, direct roll method, scraper method, knife method, extrusion method, curtain method, gravure method, rod method, dipping method, extrusion method, etc. can be cited. Among these coating methods, if the various physical properties and dryness of the non-aqueous secondary battery electrode slurry such as viscosity are considered, it is preferred to use any method selected from direct roll method, scraper method, knife method and extrusion method. This is because an electrode active material layer with a smooth surface and small uneven thickness can be obtained.
[0214] When the nonaqueous secondary battery electrode slurry is applied to both sides of the current collector, it can be applied one side at a time or both sides can be applied simultaneously. In addition, the nonaqueous secondary battery electrode slurry can be applied to the current collector continuously or intermittently.
[0215] The coating amount of the slurry for non-aqueous secondary battery electrodes can be appropriately determined according to the design capacity of the battery, the composition of the slurry for non-aqueous secondary battery electrodes, and the like.
[0216] The method for drying the nonaqueous secondary battery electrode slurry applied on the current collector is not particularly limited, and for example, methods selected from hot air, reduced pressure or vacuum environment, (far) infrared rays, and low-temperature air can be used alone or in combination.
[0217] The drying temperature and drying time when drying the non-aqueous secondary battery electrode slurry can be appropriately adjusted according to the non-volatile component concentration in the non-aqueous secondary battery electrode slurry, the coating amount to the collector, etc. The drying temperature is preferably 40° C. or higher and 350° C. or lower, and more preferably 60° C. or higher and 100° C. or lower from the viewpoint of productivity. The drying time is preferably 1 minute or higher and 30 minutes or lower.
[0218] The electrode sheet having the electrode active material layer formed on the current collector may be cut into a size and shape suitable for the electrode. The cutting method of the electrode sheet is not particularly limited, and for example, slit, laser, wire cutting, cutter, Thomson, etc. may be used.
[0219] In this embodiment, the electrode sheet may be pressed as needed before or after cutting the electrode sheet, thereby making it possible to more firmly bond the electrode active material to the current collector and reduce the thickness of the electrode, thereby miniaturizing the non-aqueous secondary battery.
[0220] As a method for pressing the electrode sheet, a general method can be used. As a pressing method, a die pressing method or a roll pressing method is particularly preferably used.
[0221] When using the die pressing method, the pressing pressure is not particularly limited, but is preferably 0.5 t / cm 2 Above and 5t / cm 2 the following.
[0222] When the roller pressing method is used, the pressing load is not particularly limited, but is preferably 0.5 t / cm to 8 t / cm, because the above-mentioned effects brought about by the pressing can be obtained while suppressing the reduction in the insertion and extraction capacity of charge carriers such as lithium ions into the electrode active material.
[0223] <6. Non-aqueous secondary batteries>
[0224] Next, a lithium ion secondary battery will be described as a preferred example of the nonaqueous secondary battery according to the present embodiment. It should be noted that the configuration of the nonaqueous secondary battery of the present invention is not limited to the example described below.
[0225] The lithium ion secondary battery of the present embodiment is a battery in which known components such as a positive electrode, a negative electrode, an electrolyte solution, and a separator which may be provided as necessary are accommodated in an outer casing.
[0226] The shape of the lithium ion secondary battery may be any shape such as a coin shape, a button shape, a sheet shape, a cylinder shape, a square shape, or a flat shape.
[0227] 〔Positive electrode / Negative electrode〕
[0228] One or both of the positive electrode and the negative electrode of the lithium ion secondary battery of this embodiment have an electrode active material layer of this embodiment containing the composite particles (P) of this embodiment. Preferably, at least the negative electrode of the positive electrode and the negative electrode of the lithium ion secondary battery of this embodiment has an electrode active material layer containing the composite particles (P).
[0229] In the lithium ion secondary battery of this embodiment, when only one of the positive and negative electrodes has an electrode active material layer containing the composite particles (P) of this embodiment, a substance containing a known binder such as polyvinylidene fluoride is used instead of the composite particles (P) of this embodiment as an electrode that does not contain the composite particles (P) of this embodiment.
[0230] 〔Electrolyte〕
[0231] As the electrolyte, a non-aqueous liquid with ion conductivity can be used. As examples of the electrolyte, a solution obtained by dissolving an electrolyte in an organic solvent, an ionic liquid, etc. can be cited, preferably the former. This is because a lithium ion secondary battery with low manufacturing cost and low internal resistance can be obtained.
[0232] As the electrolyte, an alkali metal salt can be used, and it can be appropriately selected according to the type of electrode active material. Examples of the electrolyte include LiClO4, LiBF6, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiB 10 Cl 10 , LiAlCl4, LiCl, LiBr, LiB(C2H5)4, CF3SO3Li, CH3SO3Li, LiCF3SO3, LiC4F9SO3, Li(CF3SO2)2N, aliphatic lithium carboxylate, etc. In addition, other alkali metal salts can also be used as the electrolyte.
[0233] As the organic solvent of dissolving electrolyte, it is not particularly limited, for example, carbonate compounds such as ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), fluoroethylene carbonate (FEC), vinylene carbonate (VC), nitrile compounds such as acetonitrile, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate and other carboxylic acid esters can be enumerated. These organic solvents can be used alone or in combination of two or more. Among them, as an organic solvent, it is preferred to use a material combining a straight-chain carbonate-based solvent.
[0234] [Exterior body]
[0235] As the outer casing, for example, one formed of an aluminum laminate composed of an aluminum foil and a resin film can be appropriately used, but the outer casing is not limited to these.
[0236] Example
[0237] The present invention is specifically described below by way of examples and comparative examples. It should be noted that the examples shown below are intended to facilitate understanding of the contents of the present invention. The present invention is not limited to these examples.
[0238] In the following examples, as an example of the non-aqueous secondary battery electrode of the present invention, a negative electrode of a lithium ion secondary battery is prepared, and as an example of a non-aqueous secondary battery, a lithium ion secondary battery is prepared. They are compared with the negative electrode of the lithium ion secondary battery and the lithium ion secondary battery of the comparative example to confirm the effect of the present invention.
[0239] In addition, water used in the following Examples and Comparative Examples was ion-exchanged water unless otherwise specified.
[0240] <1. Production of Binder Composition for Non-aqueous Secondary Batteries>
[0241] (Example 1 to Example 18, Comparative Example 2)
[0242] The raw material monomers (a) and thickeners shown in Tables 1 to 7 were mixed with 200 parts by mass of water as an aqueous medium (b) at the mass ratios shown in Tables 1 to 7 and emulsified to prepare monomer emulsions. Next, aqueous solutions were prepared by dissolving the free radical polymerization initiators (e) shown in Tables 1 to 7 in the amounts shown in Tables 1 to 7 in 50 parts by mass of water.
[0243] 150 parts by mass of water were added to a separable flask equipped with a cooling tube, a thermometer, a stirrer, and a dropping funnel, and the temperature was raised to 75° C. The monomer emulsion and the aqueous solution in which the radical polymerization initiator (e) was dissolved were respectively continuously supplied to the separable flask for 3 hours while stirring at 75° C. to carry out emulsion polymerization and obtain an emulsion.
[0244] The obtained emulsion was cooled to room temperature. Then, 133 parts by mass of water and 25% by mass of ammonia water (17 parts by mass of ammonia, 51 parts by mass of water) in the amount shown in Tables 1 to 7 were added to the emulsion. Thus, a non-aqueous secondary battery binder composition of Examples 1 to 18 and Comparative Example 2, which was composed of an emulsion in which the dispersed particles of Examples 1 to 18 and Comparative Example 2 were dispersed in an aqueous medium, was manufactured. The dispersed particles (composite particles) of Comparative Example 2 do not contain monomer (a2).
[0245] (Comparative Example 1)
[0246] The raw material monomers (a) shown in Table 7 were mixed with 200 parts by mass of water as an aqueous medium (b) at the mass ratio shown in Table 7 and emulsified to prepare a monomer emulsion. Next, an aqueous solution was prepared by dissolving the radical polymerization initiator (e) shown in Table 7 in the amount shown in Table 7 in 50 parts by mass of water.
[0247] 150 parts by mass of water were added to a separable flask equipped with a cooling tube, a thermometer, a stirrer, and a dropping funnel, and the temperature was raised to 75° C. The monomer emulsion and the aqueous solution in which the radical polymerization initiator (e) was dissolved were respectively continuously supplied to the separable flask for 3 hours while stirring at 75° C. to carry out emulsion polymerization and obtain an emulsion.
[0248] The obtained emulsion was cooled to room temperature. Then, 133 parts by mass of water and 25% by mass of aqueous ammonia in the amount shown in Table 7 were added to the emulsion. Thus, a non-aqueous secondary battery binder composition of Comparative Example 1 was prepared, which was composed of an emulsion in which emulsified particles containing a copolymer of Comparative Example 1 were dispersed in an aqueous medium. The emulsified particles in the emulsion of Comparative Example 1 contained a copolymer but did not contain a thickener.
[0249] (Comparative Example 3, Comparative Example 4)
[0250] Emulsions of Comparative Examples 3 and 4 were obtained in the same manner as in Comparative Example 1. The emulsified particles in these emulsions contained the copolymer but did not contain a thickener. As described later, in Comparative Examples 3 and 4, the thickener existed separately from the emulsified particles.
[0251] The obtained emulsion was cooled to room temperature. Then, the emulsion of the thickener shown in Table 7 was added to the emulsion in the amount shown in Table 7, and 123 parts by mass of water and 25% by mass of ammonia water in the amount shown in Table 7 were further added, and stirred for 30 minutes using a homodispersor. The addition amount of the emulsion AM-1000-NT in Table 7 refers to the amount of emulsified particles containing the thickener in the emulsion.
[0252] Thus, nonaqueous secondary battery binder compositions of Comparative Examples 3 and 4 were prepared, each consisting of an emulsion in which emulsified particles containing the copolymer of Comparative Example 3 or Comparative Example 4 and emulsified particles containing a thickener were independently dispersed in an aqueous medium.
[0253] It should be noted that in the binder compositions for non-aqueous secondary batteries of Comparative Examples 3 and 4, dispersion abnormalities such as agglomeration of the emulsified particles containing the copolymer and the emulsified particles containing the thickener in the composition were not observed. That is, in Comparative Examples 3 and 4, the composite particles containing the copolymer and the thickener of the present embodiment were not formed, and the binder compositions for non-aqueous secondary batteries of Comparative Examples 3 and 4 did not contain the composite particles containing the copolymer and the thickener of the present embodiment.
[0254] This is presumably because, in the non-aqueous secondary battery binder compositions of Comparative Examples 3 and 4, the emulsified particles containing the copolymer and the emulsified particles containing the thickener in the composition repel each other by charge, and thus the dispersion of the emulsified particles containing the copolymer and the emulsified particles containing the thickener in the composition is maintained.
[0255] [Table 1]
[0256]
[0257] ※1: The numerical value on the right side of the monomer (a) is the content rate (mass %) of each monomer when the total amount of the monomer is 100 parts by mass. The numerical value on the right side of the thickener is the mass fraction of the thickener when the total amount of the monomer is 100 parts by mass.
[0258] [Table 2]
[0259]
[0260] ※1: The numerical value on the right side of the monomer (a) is the content rate (mass %) of each monomer when the total amount of the monomer is 100 parts by mass. The numerical value on the right side of the thickener is the mass fraction of the thickener when the total amount of the monomer is 100 parts by mass.
[0261] [Table 3]
[0262]
[0263] ※1 The numerical value on the right column of the monomer (a) is the content rate (mass %) of each monomer when the total amount of the monomer is 100 parts by mass.
[0264] The numerical value on the right column of the thickener is the mass fraction of the thickener when the total amount of the monomers is 100 mass fractions.
[0265] [Table 4]
[0266]
[0267] ※1: The numerical value on the right side of the monomer (a) is the content rate (mass %) of each monomer when the total amount of the monomer is 100 parts by mass. The numerical value on the right side of the thickener is the mass fraction of the thickener when the total amount of the monomer is 100 parts by mass. [Table 5]
[0268]
[0269] ※1: The numerical value on the right side of the monomer (a) is the content rate (mass %) of each monomer when the total amount of the monomer is 100 parts by mass. The numerical value on the right side of the thickener is the mass fraction of the thickener when the total amount of the monomer is 100 parts by mass.
[0270] [Table 6]
[0271]
[0272] ※1: The numerical value on the right side of the monomer (a) is the content rate (mass %) of each monomer when the total amount of the monomer is 100 parts by mass. The numerical value on the right side of the thickener is the mass fraction of the thickener when the total amount of the monomer is 100 parts by mass [Table 7
[0273]
[0274] ※1: The numerical value on the right column of the monomer (a) is the content rate (mass %) of each monomer when the total amount of the monomer is 100 parts by mass.
[0275] The numerical value on the right column of the thickener is the mass fraction of the thickener when the total amount of the monomers is 100 mass fractions.
[0276] Among the monomers (a4) shown in Tables 1 to 7, polyoxyethylene alkyl ether sulfate (Aqualon KH-10, manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) is a polymerizable surfactant.
[0277] Rongalite SFS in the polymerization initiator (e) is a trade name of Rongalite manufactured by Sumitomo Seika Chemicals, Ltd.
[0278] The thickeners shown in Tables 1 to 7 are the following.
[0279] Hydrogenated petroleum resin
[0280] · Alcon M-90 (alicyclic saturated hydrocarbon resin): manufactured by Arakawa Chemical Industries, Ltd., softening point 90°C
[0281] · Alcon M-135 (alicyclic saturated hydrocarbon resin): manufactured by Arakawa Chemical Industries, Ltd., softening point 135°C
[0282] · Alcon P-90 (alicyclic saturated hydrocarbon resin): manufactured by Arakawa Chemical Industries, Ltd., softening point 90°C
[0283] · Alcon P-140 (alicyclic saturated hydrocarbon resin): manufactured by Arakawa Chemical Industries, Ltd., softening point 140°C
[0284] Emulsion AM-1000-NT (alicyclic saturated hydrocarbon resin): A dispersion obtained by dispersing a thickener similar to Alcon M-90 in water using a surfactant in an aqueous medium (concentration 50%). The numerical values described in Table 7 represent the amount of emulsified particles containing the thickener in the dispersion. Made by Arakawa Chemical Industries, Ltd., softening point 100°C
[0285] Rosin resin
[0286] · Hiroshima DS-70L (rosin ester resin): manufactured by Hiroshima Chemicals Co., Ltd., softening point 70°C
[0287] ·Horari FK-100 (disproportionated rosin ester resin): manufactured by Hiroshima Chemical Co., Ltd., softening point: 100°C
[0288] Terpene resin
[0289] ·YS Polyterpene PX800 (Polyterpene Resin): Made by YS Polytech Co., Ltd., softening point 180°C
[0290] ·YS Polyterpene PX1000 (polyterpene resin): manufactured by YSHRICA CO., LTD., softening point 100°C
[0291] The so-called addition timing shown in Tables 1 to 7 is the timing of using the tackifier in the production process of the adhesive composition. Before polymerization means that the raw material monomer (a) is copolymerized in the presence of the tackifier. After polymerization means that the tackifier is added to the emulsion containing the emulsified particles containing the copolymer obtained by copolymerizing the raw material monomer (a).
[0292] The amount of ammonia as the alkaline substance (d) shown in Tables 1 to 7 is the amount of ammonia contained in aqueous ammonia (parts by mass).
[0293] The amount of water as the aqueous medium (b) shown in Tables 1 to 7 is the total amount (parts by mass) of water contained in the binder composition for a non-aqueous secondary battery.
[0294] <2. Evaluation of composite particles and binder composition for non-aqueous secondary batteries>
[0295] The glass transition temperature (Tg) of the composite particles of Examples 1 to 18 and Comparative Examples 1 to 4 was measured by the following method. The results are shown in Tables 1 to 7.
[0296] In addition, the nonvolatile content of each of the binder compositions for nonaqueous secondary batteries of Examples 1 to 18 and Comparative Examples 1 to 4 was measured by the following method.
[0297] 〔Glass transition temperature (Tg)〕
[0298] The binder composition for a non-aqueous secondary battery was applied onto a release PET (polyethylene terephthalate) film and dried at 50° C. for 5 hours to obtain a film having a thickness of 2 mm formed of the composite particles.
[0299] A square test piece of 2 mm in length and 2 mm in width was cut out from the obtained film. The test piece was sealed in an aluminum pan, and a differential scanning calorimeter (EXSTARDSC / SS7020 manufactured by Hitachi HiTech Science Co., Ltd.) was used to perform differential scanning calorimetry (DSC) of the test piece under a nitrogen atmosphere at a heating rate of 10°C / minute. The temperature range of the DSC measurement was set to -40°C to 200°C. Furthermore, the peak temperature of the DDSC graph obtained as the temperature differential of the DSC was measured, and the temperature was set to the glass transition temperature Tg (°C) of the composite particles.
[0300] 〔Non-volatile content concentration〕
[0301] Weigh 1g of the binder composition for non-aqueous secondary batteries, place it on an aluminum dish with a diameter of 5cm, and put it in a dryer. While circulating the air in the dryer, dry it at an air pressure (1013hPa) and a temperature of 105°C for 1 hour, and measure the mass of the remaining components. Calculate the ratio (mass %) of the mass of the above-mentioned components remaining after drying to the mass (1g) of the binder composition for non-aqueous secondary batteries before drying, and set it as the non-volatile component concentration (mass %).
[0302] <3. Production of non-aqueous secondary batteries>
[0303] The nonaqueous secondary battery binder compositions of Examples 1 to 18 and Comparative Examples 1 to 4 were used to prepare negative electrodes by the following method, and lithium ion secondary batteries as nonaqueous secondary batteries of Examples 1 to 18 and Comparative Examples 1 to 4 were prepared using the negative electrodes.
[0304] [Production of positive electrode]
[0305] 94 parts by mass of LiNi 0.6 Mn 0.2 Co 0.2 O2, 3 parts by mass of acetylene black as a conductive aid, and 3 parts by mass of polyvinylidene fluoride as a binder were mixed to obtain a mixture, and 50 parts by mass of N-methylpyrrolidone was added to the obtained mixture and further mixed to obtain a positive electrode slurry.
[0306] As a positive electrode current collector, an aluminum foil with a thickness of 15 μm was prepared. The positive electrode slurry was applied to both sides of the positive electrode current collector by direct rolling. The amount of positive electrode slurry applied to the positive electrode current collector was adjusted so that the thickness per side after the roll pressing treatment described below would be 125 μm.
[0307] The positive electrode slurry coated on the positive electrode collector was dried at 120°C for 5 minutes and pressed using a roll press (manufactured by Suntech Metal, with a pressing load of 5 t / cm and a roll width of 7 cm) to obtain a positive electrode sheet having a positive electrode active material layer on both sides of the positive electrode collector. The obtained positive electrode sheet was cut into a rectangle of 50 mm in length and 40 mm in width, and a conductive sheet was connected to form a positive electrode.
[0308] [Production of negative electrode (non-aqueous secondary battery electrode)]
[0309] 96.9 parts by mass of artificial graphite (G49, manufactured by Jiangxi Zichen Technology Co., Ltd.) as a negative electrode active material, 3.6 parts by mass of any non-aqueous secondary battery binder composition manufactured in Examples 1 to 18 and Comparative Examples 1 to 4 (1.4 parts by mass of non-volatile components (binder polymer)), and 60 parts by mass of a 2% aqueous solution of CMC (carboxymethyl cellulose-sodium salt, manufactured by Nippon Paper Chemical Co., Ltd., Sanloz (registered trademark) MAC500LC) were mixed, and 16 parts by mass of water were further added, and the mixture was mixed using a rotation-revolution mixer (ARE-310, manufactured by Shinkyo Co., Ltd.) to obtain a negative electrode slurry (slurry for non-aqueous secondary battery electrodes).
[0310] A copper foil with a thickness of 10 μm was prepared as a negative electrode collector. The negative electrode slurry was applied to both sides of the negative electrode collector by direct rolling. The amount of negative electrode slurry applied to the negative electrode collector was adjusted so that the thickness of the negative electrode active material layer after the roll pressing treatment described below would be 170 μm per side.
[0311] The negative electrode slurry coated on the negative electrode collector was dried at 90°C for 10 minutes and pressed using a roller press (manufactured by Suntech Metal, with a pressing load of 8 t / cm and a roller width of 7 cm). Thus, a negative electrode sheet having a negative electrode active material layer on both sides of the negative electrode collector was obtained. The obtained negative electrode sheet was cut into a rectangle of 52 mm in length and 42 mm in width, and a conductive sheet was connected to form a negative electrode.
[0312] [Production of non-aqueous secondary batteries]
[0313] A separator (polyethylene, 25 μm thick) formed of a porous film of a polyolefin system is present between the positive electrode and the negative electrode, and the positive electrode active material layer and the negative electrode active material layer are stacked in a manner opposite to each other, and are housed in an outer body (battery pack) formed of an aluminum laminate. Then, an electrolyte is injected into the outer body, vacuum impregnation is performed, and packaging is performed using a vacuum heat sealer to obtain a lithium ion secondary battery.
[0314] As the electrolyte, a substance obtained by mixing 99 parts by mass of a solution in which LiPF6 was dissolved at a concentration of 1.0 mol / L and 1 part by mass of vinylene carbonate in a mixed solvent containing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a volume ratio of EC:EMC:DEC=30:50:20 was used.
[0315] <4. Evaluation of non-aqueous secondary batteries>
[0316] The internal resistance and the discharge capacity retention rate after 500 cycles of the lithium ion secondary batteries of Examples 1 to 18 and Comparative Examples 1 to 4 were evaluated by the following methods. The results are shown in Tables 1 to 7.
[0317] 〔Internal resistance (DCR)〕
[0318] The internal resistance (DCR (Ω)) of the lithium-ion secondary battery was measured at 25°C in the following order. That is, constant current charging was performed at 0.2C from the resting potential until the voltage reached 3.6V, making the charging state 50% of the initial capacity (SOC50%). Then, discharge was performed at current values of 0.2C, 0.5C, 1C and 2C for 60 seconds. The internal resistance DCR (Ω) at SOC50% was determined from the relationship between these four current values (values for 1 second) and voltage.
[0319] [Discharge capacity maintenance rate after 500 cycles]
[0320] Under the condition of 45°C, the series of operations of steps (i) to (iv) shown below were performed once as one cycle, and charging and discharging were performed. The time integral value of the current in steps (i) and (ii) was set as the charging capacity, and the time integral value of the current in step (iv) was set as the discharge capacity. Furthermore, the discharge capacity of the first cycle and the discharge capacity of the 500th cycle were measured, and the discharge capacity retention rate after 500 cycles was calculated by the following formula.
[0321] Discharge capacity retention rate (%) = 100 × (discharge capacity at the 500th cycle / discharge capacity at the 1st cycle)
[0322] (i) Charging at a current of 1C until the voltage reaches 4.2V (constant current (CC) charging).
[0323] (ii) Charging at a voltage of 4.2 V until the current reaches 0.05 C (constant voltage (CV) charging).
[0324] (iii) Allow to stand for 30 minutes.
[0325] (iv) Discharging at a current of 1C until the voltage reaches 2.75V (constant current (CC) discharge).
[0326] <5. Evaluation results>
[0327] As shown in Tables 1 to 7, it was confirmed that the lithium ion secondary batteries of Examples 1 to 18 had higher capacity retention rates than the lithium ion secondary batteries of Comparative Examples 1 to 4. This is presumably because the composite particles contained in the negative electrodes of the lithium ion secondary batteries of Examples 1 to 18 contain a copolymer containing structural units derived from the monomer (a1) and the monomer (a2) shown in Tables 1 to 6, and the thickener shown in Tables 1 to 6.
[0328] More specifically, in Comparative Example 1, a negative electrode was prepared using a non-aqueous secondary battery binder composition containing no thickener in which emulsified particles containing a copolymer were dispersed in an aqueous medium. Therefore, it is estimated that the binding properties between the electrode active materials and between the electrode active materials and the current collector became insufficient, resulting in a poor capacity retention rate.
[0329] In addition, in Comparative Example 2, the composite particles contained in the negative electrode include a copolymer and a thickener that do not contain a structural unit derived from the monomer (a2). Therefore, it is estimated that the effect of improving the adhesion between the electrode active materials and between the electrode active materials and the collector brought by the copolymer is insufficient, resulting in a poor capacity retention rate.
[0330] In addition, Comparative Example 3 shows a poor capacity retention rate compared to Example 1 in which a negative electrode was manufactured using a binder composition for a non-aqueous secondary battery using the same substance as the raw material monomer (a) and containing the same amount of a similar thickener. In addition, Comparative Example 4 shows a poor capacity retention rate compared to Example 18 in which a negative electrode was manufactured using a binder composition for a non-aqueous secondary battery using the same substance as the raw material monomer (a) and containing the same amount of a similar thickener.
[0331] This is presumably because the binder composition for non-aqueous secondary batteries used in Comparative Examples 3 and 4 is a substance in which a thickener is added to an emulsion containing emulsified particles containing a copolymer obtained by copolymerizing a raw material monomer (a). Therefore, the copolymer and the thickener are arranged in a separated state between the electrode active materials that form the electrode, and between the electrode active materials and the collector. As a result, the adhesion between the electrode active materials and between the electrode active materials and the collector becomes insufficient.
[0332] Furthermore, as shown in Tables 1 to 7, it was confirmed that the lithium ion secondary batteries of Examples 1 to 18 and Comparative Examples 1 to 4 had sufficiently low values for practical use from the viewpoint of internal resistance, which is a secondary effect.
[0333] Industrial Availability
[0334] The present invention provides composite particles that can be used as a binder material for forming an electrode of a non-aqueous secondary battery that can provide excellent cycle characteristics.
[0335] Explanation of symbols
[0336] 1···Copolymer
[0337] 2. Thickener
[0338] 3. Particle-like structure
[0339] 4.42···Surfactants
[0340] 10、11···Composite particles
[0341] 20···Copolymer particles.
Claims
1. A composite particle comprising a copolymer and a tackifier, The copolymer has a first structural unit derived from monomer a1 and a second structural unit derived from monomer a2, The monomer a1 is a nonionic compound having only one ethylenically unsaturated bond. The monomer a2 is a compound having a carboxyl group and having only one ethylenically unsaturated bond. 2 . The composite particles according to claim 1 , wherein at least a part of the thickener is present in a particle structure composed of chain molecules of the copolymer. 3 . The composite particles according to claim 1 , wherein the thickener is at least one resin selected from hydrogenated petroleum resins and terpene resins. The composite particles according to claim 3 , wherein the tackifier comprises a hydrogenated petroleum resin. 5 . The composite particles according to claim 4 , wherein the softening point of the hydrogenated petroleum resin is 70° C. to 140° C. The composite particles according to claim 1 , wherein the content of the thickener is 0.50 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the monomer component used in the production of the copolymer. 7 . The composite particles according to claim 1 , wherein a content of the second structural unit in all structural units of the copolymer is 0.10% by mass or more and 20% by mass or less.
8. The composite particle according to claim 1, wherein the copolymer has a third structural unit derived from monomer a3, The monomer a3 is a compound having multiple independent ethylenically unsaturated bonds. 9 . The composite particles according to claim 8 , wherein a content of the third structural unit in all structural units of the copolymer is 0.010 mass % or more and 10 mass % or less. 10 . The composite particles according to claim 1 , which are used as a binder for a non-aqueous secondary battery. 11 . A binder composition for a non-aqueous secondary battery, comprising the composite particles according to claim 1 and an aqueous medium.
12. A slurry for non-aqueous secondary battery electrodes, comprising the composite particles according to any one of claims 1 to 9, an electrode active material and an aqueous medium, The aqueous medium is one selected from water, a hydrophilic solvent, and a mixture containing water and a hydrophilic solvent. 13 . A non-aqueous secondary battery electrode comprising the composite particles according to claim 1 . 14 . A non-aqueous secondary battery comprising the non-aqueous secondary battery electrode according to claim 13 .
15. A method for producing composite particles, comprising a polymerization step of copolymerizing a raw material monomer a containing a monomer a1 and a monomer a2 in the presence of a thickener, The monomer a1 is a nonionic compound having only one ethylenically unsaturated bond. The monomer a2 is a compound having a carboxyl group and having only one ethylenically unsaturated bond.
Citation Information
Patent Citations
Puncture sealing material for tire
JP2007224248A
Water dispersion acrylic adhesive tape or sheet for transporting electronic component
JP2008285221A
Binder for lithium ion secondary battery electrodes, slurry obtained by using the binder for electrodes, electrodes obtained by using the slurry, and lithium ion secondary battery obtained by using the electrodes
JP2011243464A
Lithium ion secondary battery
JP2014239070A